The Influence of JOB Satisfaction On Teacher Performance at Omba Tana Rara State Disd Teachers - Sihang Gregorius Balimema; Adrianus kristian bayo; Susanti Gala; Zakarias aristo bora; Albertus Religius Roto (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
This study investigates the influence of job satisfaction on teacher performance at Omba Tana Rara Public School, a rural educational institution located in a geographically remote area with distinct contextual challenges. Despite the crucial role of teachers in shaping educational outcomes, limited research has explored how job satisfaction contributes to teacher performance in such isolated settings. Employing a quantitative approach, the research surveyed 32 teachers using a validated Likert-scale questionnaire designed to measure key dimensions of job satisfaction, including recognition, professional development, remuneration, interpersonal relationships, and work environment. Data analysis was conducted using simple linear regression to determine the statistical relationship between job satisfaction and teacher performance. The results revealed that job satisfaction has a significant and positive impact on teacher performance (β = 0.67; p < 0.01), indicating that increases in satisfaction levels are associated with higher levels of effectiveness and engagement among teachers. Among the satisfaction factors examined, recognition from leadership, opportunities for professional growth, and supportive working conditions were identified as dominant contributors to improved performance. The findings of this study contribute to filling the research gap concerning human resource issues in remote schools and offer practical insights for stakeholders in education. In particular, the study emphasizes the importance of designing context-specific strategies that prioritize teacher welfare as a means of boosting instructional quality and learning outcomes. It recommends policy interventions focused on enhancing intrinsic and extrinsic satisfaction elements through improved school management practices. By highlighting the correlation between teacher satisfaction and performance, especially in rural and under-resourced areas, this research underscores the need for holistic human resource development in education. It advocates for a welfare-centered approach in managing and supporting teachers to ensure sustainable improvements in school effectiveness.